PSIKOLOGI KOMUNIKASI DAN KENAKALAN REMAJA - Chyntia Devi; Eggy Satia Mulya; Hafif Try Ikhwantoro; Putri Dewi Anjani; Wira Jaya Putra Kusuma; Balqis Umati S (Jurnal Kesehatan, 2025)
Psychoeducation on the theme of ‘Communication Psychology and Juvenile Delinquency’ aims to provide vocational high school students with an understanding of the causes, effects, and solutions to deviant behaviour. This activity uses discussion, interactive lectures, and simulation methods. Evaluation results showed a significant improvement in participants' understanding, as evidenced by a Paired Sample T-Test with a p-value of <0.001. Participants became more capable of recognising emotions, building positive relationships, and resisting negative peer influence. This activity demonstrates that a communication psychology approach is effective in preventing adolescent delinquency and can be incorporated into character development programmes in schools.